Assessing the evolutionary history of the fern family Dipteridaceae (Gleicheniales) by incorporating both extant and extinct members in a combined phylogenetic study. Issue 8 (9th August 2018) - Choo, Thereis Y. S.; Escapa, Ignacio H.
Abstract : Premise of the Study: Dipteridaceae is a lineage of ferns that has existed from the early Mesozoic and is known for its extensive fossil record. By integrating information from all described extant and extinct genera into a single phylogenetic study, this paper aims to examine the taxonomy of the group on a whole and explore character evolution within the lineage across time. Methods: A morphological matrix of 51 characters was developed for 72 species (43 extinct and 29 extant) based on published information. Morphological characters were combined with nucleotide sequences for four chloroplast genes ( rbcL, atpA, atpB, and rps4 ) for extant taxa, and combined parsimony analyses were conducted to infer evolutionary trends in the group. Key Results: Dipteridaceae was found to be monophyletic and characterized by highly anastomosing minor veins forming a meshwork of areoles with free‐included veinlets. Based on our analyses, we recognize six previously described genera (i.e., Goeppertella, Thaumatopteris, Clathropteris, Digitopteris, Dipteris, and Cheiropleuria ) and one new genus (i.e., Sewardalea ). Fossils currently described as Dictyophyllum, Kenderlykia, Hausmannia, and Protorhipis are ambiguously placed on the tree and are recognized as possibly unnatural morphogenera. Conclusions: Overall, the evolutionary trend in Dipteridaceae has been toward increasing complexity in the venation pattern and laminal fusion. Only the Hausmannia ‐type frond with dichotomizing primary veins and relatively fused lamina persisted in the later part of the Mesozoic to the present. Within the crown group, we see evidence of re‐radiation of frond forms in Dipteris and Cheiropleuria .